Analysis of the biomimetic properties of niobium silicate incorporated into dental materials – literature review (Research, Society and Development, 2023)
Introduction: The development of strategies for biomimetic remineralization is presented as an extremely advantageous alternative to current restorative procedures. Niobium is a metal that, even when applied in small amounts, shows potential to improve the properties of different materials, in addition to presenting high biocompatibility and improving the physical and optical properties of these materials, in addition to presenting low toxicity. Objective: To evaluate the biomimetic properties of niobium silicate, when incorporated into dental materials, such as composite resins, cements and adhesives. Methodology: An integrative literature review was carried out in the PubMed, SCIELO and Google Scholar databases with the descriptors: Niobium Silicate, Biomimetics, Dental Materials and Dentistry. Results: Information was found in the literature indicating that Niobium Silicate is a viable alternative in the study of bioactive agents added to dental materials. Conclusion: Given the above, it can be concluded that niobium silicate presents satisfactory results and biocompatible characteristics when incorporated into composite resin, resin cement, adhesives and dental substrate.